Effects of Ozone Isotopologue Formation on the Clumped‐Isotope Composition of Atmospheric O2. Issue 14 (19th July 2021) - Yeung, Laurence Y.; Murray, Lee T.; Banerjee, Asmita; Tie, Xin; Yan, Yuzhen; Atlas, Elliot L.; Schauffler, Sue M.; Boering, Kristie A.
Abstract: Tropospheric 18 O 18 O is an emerging proxy for past tropospheric ozone and free‐tropospheric temperatures. The basis of these applications is the idea that isotope‐exchange reactions in the atmosphere drive 18 O 18 O abundances toward isotopic equilibrium. However, previous work used an offline box‐model framework to explain the 18 O 18 O budget, approximating the interplay of atmospheric chemistry and transport. This approach, while convenient, has poorly characterized uncertainties. To investigate these uncertainties, and to broaden the applicability of the 18 O 18 O proxy, we developed a scheme to simulate atmospheric 18 O 18 O abundances (quantified as ∆36 values) online within the GEOS‐Chem chemical transport model. These results are compared to both new and previously published atmospheric observations from the surface to 33 km. Simulations using a simplified O2 isotopic equilibration scheme within GEOS‐Chem show quantitative agreement with measurements only in the middle stratosphere; modeled ∆36 values are too high elsewhere. Investigations using a comprehensive model of the O‐O2 ‐O3 isotopic photochemical system and proof‐of‐principle experiments suggest that the simple equilibration scheme omits an important pressure dependence to ∆36 values: the anomalously efficient titration of 18 O 18 O to form ozone. Incorporating these effects into the online ∆36 calculation scheme in GEOS‐Chem yields quantitative agreement for all available observations. While this previously unidentified bias affects the atmospheric budget of 18 O 18 O in O2, the modeled change in the mean tropospheric ∆36 value since 1850 CE is only slightly altered; it is still quantitatively consistent with the ice‐core ∆36 record, implying that the tropospheric ozone burden increased less than 40% over the twentieth century. Plain Language Summary: Oxygen in the air is constantly being broken apart and remade. Its constituent atoms are shuffled around by light‐induced chemical reactions, which cause changes in the number of heavy oxygen atoms that are bound together. The number of these heavy‐atom "clumps" is sensitive to air temperatures and the presence of air pollution; hence, their variations are being used to understand past high‐altitude temperatures and atmospheric chemistry. This study incorporates oxygen clumping into an atmospheric chemistry model and compares the results to measurements of oxygen clumping in the atmosphere. We find that the model can explain all the modern‐day measurements (from the surface to 33 km altitude), but only if the broader fates of oxygen atoms–that is, their incorporation into other molecules beyond O2 –are considered. Simulations of the preindustrial atmosphere are also generally consistent with snapshots of the ancient atmosphere obtained from O2 trapped in ice cores. The developments described herein will thus enable models to simulate heavy oxygen‐atom clumping in past cold and warm climates and enable simulated high‐altitude atmospheric changes to be evaluated directly against ice‐core snapshots of the ancient atmosphere. Key Points: Online calculations of atmospheric 18 O 18 O variations have been implemented in GEOS‐Chem, which reproduces all atmospheric observations well Titration of 18 O 18 O into heavy ozone was determined to be an important missing component of previous 18 O 18 O budgets Change in atmospheric 18 O 18 O abundance since 1850 CE is still consistent with <40% increase in tropospheric ozone burden